Oltre il nichilismo - Cucci, Giovanni ca. 20./21. Jh. (La civiltà cattolica, 2021)
The current pandemic, in addition to its various consequences, has also had the effect of calling into question the silence on the “ultimate questions”, typical of the nihilistic view of life that has dominated the cultural horizon of the West in recent decades. According to this conception, in fact, man would not be able to access the truth, because there are no stable values. This is a consequence of the death of God and of a fragmented vision of time and history. The emergence of these times has instead urgently re-proposed the irrepressible demand for stability at various levels, whether it be cognitive, ethical, or affective, contesting the assumptions of nihilism point by point.